Regulation of glucose metabolism: Effects on oocyte, preimplantation embryo, assisted reproductive technology and embryonic stem cell - Yu-Ying Xiong; Hai-Ying Zhu; Ruo-Jin Shi; Yun-Feng Wu; Yong Fan; Long Jin (Heliyon, 2024)
Glucose is a major energy substrate for cellular life activities, and its metabolic pathways include glycolysis, the pentose phosphate pathway, the hexosamine biosynthesis pathway, and the polyol pathway. Here, we review the glucose uptake pathways, metabolic characteristics, glucose transport, glucose metabolism-related enzymes, and biological importance in mammalian oocyte maturation, early embryo development, and embryonic stem cell proliferation and differentiation. Moreover, the interrelationships among glucose metabolism, female reproduction-related diseases and assisted reproductive technologies are focused. In addition, we review a number of analytical methodologies with the intention to integrate a multi-tiered strategy that encompasses cutting-edge metabolomics, artificial intelligence, epigenetics, and morphological assessments, setting the stage for a pivotal approach to cultivating high-caliber embryos in the future.